No association between obstructive sleep apnea and restless legs syndrome: results from a large hospital-based cross-sectional study - Øverland, Erik Vevatne; Waaraas, August; Lundetræ, Ragnhild S.; Lehmann, Sverre; Saxvig, Ingvild W.; Bjorvatn, Bjørn (Frontiers in Sleep, 2025)
IntroductionSome studies have indicated a possible association between obstructive sleep apnea (OSA) and restless legs syndrome (RLS). Our aim was to explore this association in a large sample of patients referred to a hospital for suspected OSA.MethodsThe sample included 8,852 patients referred to Haukeland University Hospital with suspicion of OSA between 2011 and 2022. OSA was diagnosed and categorized using standard respiratory polygraphy. Prior to the sleep study the patients completed an extensive questionnaire, including questions to determine if they had RLS. Pearson chi-square tests were used to examine RLS in relation to the presence and severity of OSA. Two separate logistic regression analyses were conducted. The first with moderate-severe OSA as the dependent variable and RLS as predictor, the second with RLS as the dependent variable and OSA severity as predictor. Both were adjusted for sex, age, marital status, alcohol consumption, daily smoking, caffeine after 17:00, and body mass index ≥30.ResultsIn total, 24.0% fulfilled the criteria for RLS, whereas moderate-severe OSA (apnea-hypopnea-index ≥15) occurred in 38.1% of the patients. The proportion of patients with RLS did not differ depending on OSA severity. Furthermore, there was no association between RLS and OSA in either chi-square or logistic regression analyses.ConclusionThe present study did not show increased prevalence of RLS in patients with OSA compared to patients without OSA. Furthermore, we found no increase in prevalence of RLS with increasing OSA severity. This suggests that these two sleep disorders are independent of each other.